Design and simulation of Zeonex Based Suspended Microstructure Photonic Crystal Fiber for Chemical Sensing Application - Islam, Md Rakibul; Ritu, Tabassum Jannat; Ullah, Saeed Mahmud (Dhaka University Journal of Applied Science and Engineering, 2023)
Over the last few years for sensing applications in terahertz regime photonic crystal fiber (PCF) has gained attention quite extensively. The optical characteristics of photonic crystal fiber can be controlled by fine-tuning of the structural parameters like core radius and effecctive area. In this context, a terahertz sensor based on a hollow-core photonic crystal fiber has been developed for chemical identification in the terahertz frequency range with very low loss. The proposed structure contains hexagonal manner sectored suspension type cladding and hexagonal manner sectored core region, all the sector are formed by zeonex based struts. To investigate the optical characteristics of developed design, finite element method (FEM) based COMSOL multiphysics v.5.4a software has been used. The simulation result shows the sensitivity of 83.37% and 83.63% at the optimum condition in x-polarization mode for ethanol and benzene respectively with low effective material loss of 0.0291 cm−1 and low confinement loss of 1.87×10-13 cm-1. Moreover, the developed design implementation is possible in the existing fabrication method. Physical features and comparative performance analysis are also showed in this research. DUJASE Vol. 7 (2) 56-61, 2022 (July)